Burden of Illness in Geographic Atrophy: A Study of Vision-Related Quality of Life and Health Care Resource Use - Patel PJ (Dove Medical Press, 2020)
Praveen J Patel,1 Focke Ziemssen,2 Eugene Ng,3 Anushini Muthutantri,4 David Silverman,5 Elizabeth A Tschosik,6 Ronald A Cantrell6 1NIHR Biomedical Research Centre at Moorfields Eye Hospital NHS Foundation Trust, and University College London Institute of Ophthalmology, London, UK; 2University of Tuebingen, Tuebingen, Germany; 3Institute of Eye Surgery, UPMC Whitfield and Waterford Institute of Technology, Waterford, Ireland; 4IQVIA, London, UK; 5Roche Products Limited, Welwyn Garden City, Hertfordshire, UK; 6Genentech, Inc., A Member of the Roche Group, South San Francisco, CA, USACorrespondence: David SilvermanOphthalmology, Roche Products Limited, 6 Falcon Way, Shire Park, Welwyn Garden City AL7 1TW, UKTel +44 1707 36 6394Email david.silverman@roche.comPurpose: To gain comprehensive information on the burden of illness due to geographic atrophy (GA).Methods: This cross-sectional study with a retrospective chart review involved patients aged ≥70 years with physician-confirmed bilateral symptomatic GA due to age-related macular degeneration (GA group), as well as patients of similar age with no ophthalmic condition that in the opinion of the investigator affected visual function (non-GA group). Data relating to patients’ current disease status and sociodemographics were self-reported on patient questionnaires at study entry and extracted from patient charts. Historical data on health care resource utilization (HCRU) were also collected via patient questionnaires and retrospective chart review (GA group only). Overall vision-related functioning and quality of life (QoL) were compared between the GA and non-GA groups using the National Eye Institute Visual Function Questionnaire-25 (NEI-VFQ-25) composite and subscales, and change in vision over the past year was assessed using the Global Rating of Change Scale.Results: Vision-related functioning and QoL were poorer in patients with vs without GA (n=137 vs 52), as demonstrated by significantly lower NEI-VFQ-25 composite score (mean, 53.1 vs 84.5 points, respectively; P<0.001), as well as lower subscale scores for near activities, distance activities, dependency, driving, social functioning, mental health, role difficulties, color vision, and peripheral vision. Substantially more patients with GA than without GA reported worsening in vision over the past year (82% vs 25%, respectively; odds ratio, 13.55; P<0.001). In the GA group, associated mean annual costs for direct ophthalmological resource use per patient amounted to €1772 (mostly for tests/procedures), and for indirect ophthalmological resource use, €410 (mostly for general practitioner visits).Conclusion: Patients with GA experience a poorer level of vision-related function and QoL than their peers, especially in relation to driving. GA is also associated with notable HCRU/associated costs, mostly direct costs attributed to diagnostic tests/procedures.Keywords: burden of illness, geographic atrophy, vision-related quality of life, health care resource utilization, visual function, health care costs